2003
DOI: 10.1046/j.1469-8137.2003.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen fungi have low cyanobiont selectivity in maritime Antarctica

Abstract: Summary• The cyanobionts of lichens and free-living Nostoc strains from Livingston Island (maritime Antarctica) were examined to determine both the cyanobiont specificity of lichens and the spatial distribution of Nostoc strains under extreme environmental conditions.• We collected five different lichen species with cyanobacteria as primary or secondary photobiont ( Massalongia carnosa , Leptogium puberulum , Psoroma cinnamomeum , Placopsis parellina and Placopsis contortuplicata ) and free-living cyanobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 25 publications
7
87
4
Order By: Relevance
“…These results contradict earlier studies, based on smaller datasets, which suggested that species-level host specialization was prevalent in cyanolichens and that host species was a better predictor of symbiont genotype than geography (Paulsrud et al, , 2000. Wirtz et al (2003) suggested that the lack of host specialization observed in Antarctic cyanolichens might be due to selection pressure for generalism in harsh environments, but our data indicate that low host specialization can be found also in temperate cyanolichens. Given the differences in photobiont specificity documented even among closely related species of green algal lichens (Yahr et al, 2004), it would be advisable to conduct careful studies on a case-by-case basis for a broad sampling of lichen species before drawing general conclusions about host specialization.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results contradict earlier studies, based on smaller datasets, which suggested that species-level host specialization was prevalent in cyanolichens and that host species was a better predictor of symbiont genotype than geography (Paulsrud et al, , 2000. Wirtz et al (2003) suggested that the lack of host specialization observed in Antarctic cyanolichens might be due to selection pressure for generalism in harsh environments, but our data indicate that low host specialization can be found also in temperate cyanolichens. Given the differences in photobiont specificity documented even among closely related species of green algal lichens (Yahr et al, 2004), it would be advisable to conduct careful studies on a case-by-case basis for a broad sampling of lichen species before drawing general conclusions about host specialization.…”
Section: Discussioncontrasting
confidence: 99%
“…This is true both for sexual species with horizontal photobiont transmission (P. canina, P. membranacea, P. rufescens) and for species that produce specialized asexually derived codispersal propagules (P. didactyla). Sharing of photobiont genotypes among different host species has also been reported previously among members of the Nephromataceae (Rikkinen et al, 2002;Lohtander et al, 2003;Wirtz et al, 2003), as well as within bryophytes (Costa et al, 2001) and cycads (Costa et al, 1999), but ours is the first study to include large enough sample sizes of both plant symbionts and lichen photobionts to infer that symbiont sharing among unrelated hosts is common. These results contradict earlier studies, based on smaller datasets, which suggested that species-level host specialization was prevalent in cyanolichens and that host species was a better predictor of symbiont genotype than geography (Paulsrud et al, , 2000.…”
Section: Discussionsupporting
confidence: 82%
“…The geographical scope of earlier studies was expanded considerably by Wirtz et al (2003) who identified cyanobacterial trnL genotypes from five cyanolichen species and free-living Nostoc colonies collected from several localities in two ice-free inland habitats on Livingston Island, maritime Antarctica. Lichen specimens from polar environments had not been analyzed in previous studies (Fig.…”
Section: From Single Thalli To Global Distribution Patternsmentioning
confidence: 99%
“…Ohridski" on Livingston Island in the South Shetland Islands (Maritime Antarctica) -during the Bulgarian Antarctic expedition 2006/07 (Tosi et al, 2010). Published data about the filamentous and larger fungi of Livingston Island are scarce (Gray & Smith 1984;Wirtz et al, 2003). Furthermore, the filamentous fungi from the Bulgarian area on Livingston Island have only been investigated by our research team.…”
Section: Introductionmentioning
confidence: 99%